A proposed nomenclature for biological processes that remove nitrogen. Issue 1 (2nd December 2016) - Weißbach, Max; Criddle, Craig S.; Drewes, Jörg E.; Koch, Konrad
Abstract : A consistent terminology is proposed to resolve present inconsistencies and to facilitate distinct communication about biological nitrogen removal processes. Abstract : For development and optimization of novel biological nutrient removal processes, factors affecting energy and greenhouse gas emissions ( e.g. nitrous oxide) are increasingly important. Energy efficient pathways are exploited, such as short-cut processes for treatment of concentrated side streams. These pathways are usually well described, but a consistent nomenclature is still lacking: some functionally equivalent processes are referred to using distinct names, and some functionally distinct processes are referred to with the same name. To address this issue, we propose a standardized terminology, in which a root term designates the end product for oxidation pathways or the reactant for reduction pathways; a qualifier is used to designate the predominant oxidation–reduction regime (ORR) and an optional indicator is used to designate partial turnover rates, e.g. partial ammonia oxidation to nitrite.